PENERAPAN ARSITEKTUR METAFORA PADA PERANCANGAN BANGUNAN KONSERVASI FLORA INDONESIA DI KOTA TANGERANG, BANTEN - Achmad Hermanto; Tri Endangsih; Inggit Musdinar Sayekti Sihing Yang Mawantu (MAESTRO, 2023)
Recently, the issue of air pollution is being discussed because it is a problem that must be addressed immediately, especially in the Capital Region of Jakarta and its surroundings, Jabodetabek is the area with the highest level of air pollution in Indonesia, including the city of Tangerang. The right handling of air pollution is to balance or fulfill green open spaces that are overgrown with many plants, to absorb carbon dioxide that causes air pollution. Flora Conservation Building is a building used for efforts to maintain, utilize, and preserve plants, so that these plants are preserved, besides that it is a place for the general public to learn about plants so that, the general public can plant trees in their respective homes properly and correctly. By planting trees in each house, the need for private green open space will be fulfilled and can reduce the number of air pollution in the city of Tangerang. In addition to making the building a place for plant education, the Conservation Building will also be built as an iconic recreational place for the people of Tangerang city, with the application of Metaphor Architecture to each building mass in the conservation area will make the existing buildings into buildings that are easily remembered and recognized by the general public.